Scintillation characteristics of the single crystalline CdWO₄ and Bi₄Ge₃O₁₂ compounds doped with mercury-like ions - Zorenko, Yu.; Limarenko, L.; Konstankevych, I.; Pashkovsky, M.; Moroz, Z.; Solsky, I.; Grinev, B.; Nekrasov, V.; Borodenko, Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Investigated are optical, luminescent and light-technical properties of the CdWO₄ and Bi₄Ge₃O₁₂ single crystals doped with mercury-like Bi³⁺ and Pb²⁺ impurities, respectively, with the aim of assertaining the possibility to match their spectral characteristics with a spectral sensitivity of semiconductor radiation detectors. It is established that the long-wave shift of the CdWO₄:Bi emission spectra and increase of the light yield in the sensitivity region of Si-PD up to 15-20% in comparison with this parameter for the CdWO₄, occuring at optimal level of the activator concentration 0.025–0.25 mass% Bi₂O₃ in the melt and contens of Li⁺ or Ag⁺ ions as compensators for providing the ratio of mentioned impurities not less than 1:(1.5÷3), is connected with emission of the (BiO₆⁹⁻) complexes with lmax = 560 nm and t = 0.8-4.2 µs at 300 K. The shift of the emission spectra of the Bi₄Ge₃O₁₂:Pb crystals into the red spectral region is caused by emission of the (PbO₆¹⁰⁻) complexes in the bands with lmax = 570 and 690 nm and t = 1.0 ms. In addition, the light yield of the Bi₄Ge₃O₁₂:Pb single crystals at impurity concentrations of 0.005–0.5 mass% PbO in the melt was not less than 1.0–0.8 in comparison with that of undoped analogs.